Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/829496
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of As-Annealed TiO2Nanotubes Doped with Ag Nanoparticles against Periodontal Pathogens

Abstract: It is important to develop functional transmucosal implant surfaces that reduce the number of initially adhering bacteria and they need to be modified to improve the anti-bacterial performance. Commercially pure Ti sheets were anodized in an electrolyte containing ethylene glycol, distilled water and ammonium fluoride at room temperature to produce TiO2 nanotubes. These structures were then annealed at 450°C to transform them to anatase. As-annealed TiO2 nanotubes were then treated in an electrolyte containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…21, 22, 23, 24, 25, 26, 27, 28, 29, 30 In addition, dental composites containing nanoparticles of silver (NAg) have been developed to achieve antibacterial activities. 31, 32, 33, 34, 35 Incorporating NAg with a high surface area into the resin is desirable to reduce the Ag filler level required for antibacterial efficacy. This approach enables a high antibacterial activity at a low Ag filler level, without compromising the composite colour and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…21, 22, 23, 24, 25, 26, 27, 28, 29, 30 In addition, dental composites containing nanoparticles of silver (NAg) have been developed to achieve antibacterial activities. 31, 32, 33, 34, 35 Incorporating NAg with a high surface area into the resin is desirable to reduce the Ag filler level required for antibacterial efficacy. This approach enables a high antibacterial activity at a low Ag filler level, without compromising the composite colour and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, the synthesis of Ag NPs onto TiO 2 nanotubes requires careful consideration, especially when a clinical application is considered. [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Silver nanoparticles can be synthesised using a variety of techniques such as electrochemical method [20], thermal decomposition [18], and laser ablation [22]. However, chemical reduction is one of the simplest method of fabricating Ag NPs on to the surface of TiO 2 nanotubes, whereby a reducing agent is used to reduce the silver ions to Ag NPs [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Titania nanotubes can provide abundant space to improve osteogenic activity and can act as carriers for drug delivery. [17][18][19] A previous study showed that nanotubes can exhibit moderate antibacterial ability. 17 Tetracycline (TET), a broad-spectrum antibiotic, can inhibit gram-negative and some gram-positive pathogens.…”
Section: Introductionmentioning
confidence: 99%